2007
DOI: 10.1590/s1807-59322007000300007
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Dispensing Errors in the Hospital Pharmacy

Abstract: Anacleto TA, Perini E, Rosa MB, César CC. Drug-dispensing errors in the hospital pharmacy. Clinics.2007;62(3):243-50. OBJECTIVE:To determine the dispensing error rate and to identify factors associated with them, and to propose prevention actions. METHODS: A cross-sectional study focusing on the occurrence of dispensing errors in a general hospital in Belo Horizonte that uses a mixed system (a combination of multidose and unit dose systems) of collective and individualized dosing. RESULTS: A total of 422 presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 13 publications
2
47
0
8
Order By: Relevance
“…[3, In some research papers mixed methods were used to determine the incidence and causes of dispensing errors. [15,30,43,65] Table 3 [3, [64][65][66][67][68][69][70][71] summarizes the research methods employed by the identified research papers. This review has identified that the majority (88%, n = 21) of UK research papers employed incident report forms to investigate dispensing errors.…”
Section: Methodsmentioning
confidence: 99%
“…[3, In some research papers mixed methods were used to determine the incidence and causes of dispensing errors. [15,30,43,65] Table 3 [3, [64][65][66][67][68][69][70][71] summarizes the research methods employed by the identified research papers. This review has identified that the majority (88%, n = 21) of UK research papers employed incident report forms to investigate dispensing errors.…”
Section: Methodsmentioning
confidence: 99%
“…Further decentralization, adequate manpower deployment and staff training on DE will minimize dispensing mistakes and uncertainty. [14] Interprofessional teamwork was rated average (Scale: 2.18). However, in real work situation, hospital pharmacists in Nigeria are yet to be integrated as vital members of health care delivery at ward level, since the clinical pharmacy practice is still rudimentary in Nigeria hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…[12,13] DE at work tend to increase with high level of interruption, distraction, noise, exhaustion, illegible doctor's prescription, failure to check patient's name with prescription, wrong dose calculation, absent-mindedness, incorrect drug, poor labels, wrong time of dispensing, talkative patients or clients and patients in a hurry. [2,[13][14][15][16][17] Pharmacist's error could be mechanical or judgmental. [18] Other DE could be errors of omission or commission.…”
Section: Dispensing Errorsmentioning
confidence: 99%
“…Medication errors accounted for 50% of adverse events detected in a study carried out in a private hospital in the city of Campinas (São Paulo State) 14 . In anoother study performed in a public hospital in the city of Belo Horizonte (Minas Gerais State), 82% of 422 prescription order forms presented at least one dispensing error 15 . Administrative errors represented about 27% of adverse events identified in a Brazilian multi-centre study 16 .…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, every year, millions of prescriptions do not follow the legal requirements that are necessary to guarantee correct dispensing and administration of medication 18 . Moreover, different studies have shown that the inadequacies of prescriptions and the difficulties in understanding them risk patient safety 1,15,19 . Therefore, the aims of this study were to analyze the quality of prescriptions at four Brazilian hospitals and to identify possible errors caused by inadequacies.…”
Section: Introductionmentioning
confidence: 99%